Characteristics of Hepatitis B Virus Genotype and Sub-Genotype in Hepatocellular Cancer Patients in Vietnam - Phat Tan Ho; Mario Giosuè Balzanelli; Pietro Distratis; Rita Lazzaro; Duy Khanh Tran; Kieu C. D. Nguyen; Tri Minh Bui; Thinh Tien Nguyen; Son Truong Pham; Huy Song Dinh Nguyen; Vinh Thanh Tran; Toan Trong Ho; et al. (Diagnostics, 2022)
Untreated chronic hepatitis B virus (HBV) infection can lead to chronic liver disease and may progress to cirrhosis or hepatocellular carcinoma (HCC). HBV infection has been prevalent in Vietnam, but there is little information available on the genotypes, sub-genotypes, and mutations of HBV in patients with HBV-related HCC confirmed by histopathological diagnosis. We studied the molecular characteristics of HBV and its genetic variants in Vietnamese HCC patients after liver tumor resection. We conducted a descriptive cross-sectional study on 107 HBV-related HCC hospitalized patients from October 2018 to April 2019. The specimens collected included EDTA anticoagulant blood and liver tissues. Extracted HBV DNA was subjected to whole genome sequencing by the Sanger method. We discovered 62 individuals (57.9%) with genotype B and 45 patients (42.1%) with genotype C, with only sub-genotypes B4 and C1. Among the mutations, the double mutation, A1762T-G1764A, had the most significant frequency (73/107 samples; 68.2%) and was higher in genotype C than in genotype B (p < 0.001). The most common genotypes found in HCC patients in this investigation were B and C, with sub-genotypes B4 and C1 for each. The prevalence of genotype B4 was greater in HBV-infected Vietnamese HCC patients.